Remembering for the future: Feminicide literary narratives and the formation of feminist collective subjects - Forchieri, Sofía (Memory studies, 2025)
Over the past three decades, transnational feminist activist movements in Latin America have been struggling to construct collective subject positions from where to remember, bear witness to, and rally against feminicide. This article explores literature’s contribution to this broader process of feminist collective subjectivity formation. It does so by means of a reading of two recent yet already emblematic feminicide narratives in literature: Selva Almada’s Dead Girls and Cristina Rivera Garza’s Liliana’s Invincible Summer. The article starts by making a case for the importance of attending to the rhetorical dimensions of contemporary literary engagements with feminicide to better understand how they mobilize memory with a view to enabling political change. Subsequently, the analysis shows how, in the process of commemorating gender violence, Almada and Rivera Garza tactically interpellate readers into communities of feminicide remembrance with the aim of bolstering ongoing feminist struggles against gender violence.